Training on the Utilization of Spices as a Mixed Variant for Mocktail Drinks for PKK Organizations RW 09 Prima Harapan Regency Bekasi - Lilik Edi Saputro; Kasmin; Donna Ekawaty; Syaharuddin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Mocktail drinks are a type of non-alcoholic drink made by mixing fruit juices and other soft drinks. Spices are parts of plants that are used as seasonings, flavor enhancers, fragrances, and food preservatives that are used on a limited basis. The PKK RW 09 Prima Harapan Regency organization is part of the Family Welfare Empowerment Movement (PKK) which operates in the Rukun Warga (RW) 09 area, they carry out various activities and programs, such as skills training, health counseling, education, environmental management, and programs other social programs. Through the activities and programs implemented, PKK RW 09 Prima Harapan Regency strives to create a clean, healthy and environmentally friendly environment, as well as increasing the capacity and skills of community members so that they can be independent and contribute positively to local development.